Long term safety and visibility of a novel liquid fiducial marker for use in image guided radiotherapy of non-small cell lung cancer - Steen Riisgaard de Blanck; Jonas Scherman Rydhög; Klaus Richter Larsen; Paul Frost Clementsen; Mirjana Josipovic; Marianne Camille Aznar; Per Munck af Rosenschöld; Rasmus Irming Jølck; Lena Specht; Thomas Lars Andresen; Gitte Fredberg Persson (Clinical and Translational Radiation Oncology, 2018)
Safety and clinical feasibility of injecting a novel liquid fiducial marker for use in image guided radiotherapy in 15 patients with non-small cell lung cancer are reported. No major safety or toxicity issues were encountered. Markers present at start of radiotherapy remained visible in cone beam computed tomography and fluoroscopy images throughout the treatment course and on computed tomography images during follow-up (0–38 months). Marker volume reduction was seen until 9 months after treatment, after which no further marker breakdown was found. No post-treatment migration or marker related complications were found. Keywords: Liquid fiducial marker, Image-guided radiotherapy, NSCLC, Endoscopic ultrasound, EBUS